The Value of Combined Detection Using Four Methods for Early Diagnosis of Active Tuberculosis - Pu, Jie; Yang, Shuangyin; Wang, Pu (Journal of Contemporary Medical Practice, 2025)
Objective: To evaluate the diagnostic value of combining Interferon-gamma Release Assay (IGRA), CD161 flow cytometry, GeneXpert MTB/RIF assay (Xpert), and Tuberculin Skin Test (TST) for early diagnosis of active pulmonary tuberculosis (PTB). Methods: A total of 289 patients (139 with active PTB and 150 with other pulmonary diseases) admitted between August 2023 and August 2024 were enrolled. All participants underwent IGRA, Xpert, TST, CD161 flow cytometry, and Erythrocyte Sedimentation Rate (ESR) testing. Chi-square tests were used to compare positive rates between groups. Receiver Operating Characteristic (ROC) curves were generated to analyze the diagnostic performance (Area Under the Curve, AUC) of individual and combined methods. Results: IGRA demonstrated the highest sensitivity (91.4%) but lower specificity (61.3%). Xpert exhibited optimal specificity (99.3%) and positive predictive value (98.8%) but limited sensitivity (59.7%). The combined use of four methods achieved an AUC of 0.933 (95% CI: 0.905–0.962), significantly surpassing individual methods (IGRA: 0.764; Xpert: 0.795; TST: 0.638; CD161: 0.626). ESR was excluded from combined analysis due to its inability to differentiate active PTB from other pulmonary diseases. Conclusion: While individual methods exhibit limitations, the combination of IGRA, Xpert, TST, and CD161 flow cytometry significantly improves diagnostic accuracy for active PTB, offering critical support for early clinical decision-making.